2013
DOI: 10.1038/tp.2013.16
|View full text |Cite
|
Sign up to set email alerts
|

Maternal immune activation and strain specific interactions in the development of autism-like behaviors in mice

Abstract: It is becoming increasingly apparent that the causes of autism spectrum disorders (ASD) are due to both genetic and environmental factors. Animal studies provide important translational models for elucidating specific genetic or environmental factors that contribute to ASD-related behavioral deficits. For example, mouse research has demonstrated a link between maternal immune activation and the expression of ASD-like behaviors. Although these studies have provided insights into the potential causes of ASD, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(191 citation statements)
references
References 56 publications
15
167
1
Order By: Relevance
“…[51][52][53][54][55] Furthermore, maternal exposure during pregnancy to various pathogens and/or the maternal immune response (fever, inflammation) have been associated with significant increased risk of autism spectrum disorder (ASD). [56][57][58][59] In this regard, gestational exposure to the viral mimetic poly(I:C) in rodents resulted in ASD-like behavioral abnormalities in the progeny, 60 and immune cells from the same animals had OXPHOS deficits still present in adulthood. 61 These findings are consistent with the current view of chronic inflammation in which the proinflammatory-phase response (mainly fueled by ATP generated in glycolysis 13 ) predominates and persists unless external changes are implemented.…”
Section: Figurementioning
confidence: 99%
“…[51][52][53][54][55] Furthermore, maternal exposure during pregnancy to various pathogens and/or the maternal immune response (fever, inflammation) have been associated with significant increased risk of autism spectrum disorder (ASD). [56][57][58][59] In this regard, gestational exposure to the viral mimetic poly(I:C) in rodents resulted in ASD-like behavioral abnormalities in the progeny, 60 and immune cells from the same animals had OXPHOS deficits still present in adulthood. 61 These findings are consistent with the current view of chronic inflammation in which the proinflammatory-phase response (mainly fueled by ATP generated in glycolysis 13 ) predominates and persists unless external changes are implemented.…”
Section: Figurementioning
confidence: 99%
“…Repetitive behaviors in mice include unusually long bouts of self-grooming, digging, and burying foreign objects such as marbles. High levels of stereotyped or repetitive behaviors have been reported in mice with mutations in genes including Shank3 [15], 16p11.2 deletion [28,54], Cntnap2 [17], and Ephrin-A [27] in the inbred strains of BTBR [6,[55][56][57], C58/J [58], and in deer mice [59].…”
Section: Discoveries Of Autism-relevant Behaviors In Mouse Modelsmentioning
confidence: 99%
“…So far, the effect of MIA is mostly replicated in wild-type C57BL/6N mice 8,10,13,16 . Others have also observed the MIA effect in BTBR mouse strain 19 . It has been shown that poly(I:C) could elicit different immune responses in genetically engineered mice 13,[22][23][24] , which may introduce additional confounding effects to the offspring.…”
Section: Representative Resultsmentioning
confidence: 98%
“…Furthermore, therapeutic and prophylactic strategies are also developed from this model system 13,16,17 . By inducing MIA at E12.5, others have shown that MIA produces fetal microglial activation and cholinergic developmental alteration in basal forebrain 18 , strain specific interaction 19 , brain cerebral synaptosomal ultrastructural abnormalities, cerebral mitochondrial respiratory chain hyperfunction abnormalties, downregulation of cerebral synaptosomal molecules 17 , depressive-like behaviors, impairment in cognition and hippocampal longterm potentiation (LTP), and deficit of adult hippocampal neurogenesis 1. Weigh the mouse on the scale and put it back into the cage.…”
Section: Introductionmentioning
confidence: 99%